INTERNATIONAL COOPERATION IN THE FIELD OF CULTURE UNDER THE CONDITIONS OF THE RUSSIAN-UKRAINIAN WAR: CULTURAL ASPECT - Maslikova, Iryna (Ukrainian Cultural Studies, 2023)
The article analyzes the experience of international cooperation in the field of culture during the Russian-Ukrainian war. Significantachievements in international cooperation by the means of culture resulted in the institutionalization of cultural diplomacy as a tool of the culturalpolicy of "soft power". Cultural diplomacy includes the exchange of ideas, information, and cultural goods between peoples in order to fostermutual understanding. Thanks to the United24 platform and the Ukrainian Institute, large-scale projects have been implemented last year. Theseprojects aimed at helping victims of war, their rehabilitation, rebuilding cultural infrastructure, Ukraine's involvement in weighty cultural events andprocesses, and the presentation of Ukrainian culture to the world. Informational, volunteer, rehabilitation, sanctions, diplomatic activities in the fieldof culture in wartime conditions proved that cultural diplomacy is an effective tool of cultural, humanitarian and security policies. Realization of themain goal of Ukrainian cultural diplomacy – the expansion of Ukraine's recognition abroad is impossible without awareness of the value basis ofUkrainian culture and the belonging of the Ukrainian people to a broad cultural and political context. The issue of the cultural identity of Ukrainiansis connected with the colonial past of Ukraine, the aggressive expansion of Russia. The revaluation of the cultural role of Russia gained urgentrelevance against the background of the war and, on the one hand, led to the practices of "the cancel culture". This practice is important to ensurethat there are no attempts to apparently balance the victims of Ukrainians and Russians in the war, the anonymity of the true victims and the lack offair retribution for criminals, the silencing of the truth, and war fatigue. On the other hand, such processes aggravated the issue of various "others",who will be able to unite on the basis of a common contemporary Ukrainian culture after the war. Therefore, in order to clarify the specifics ofcultural identity, a number of cultural problems arise that require a theoretical solution (the nature of cultural identity, the constitution of culturalsubjectivity in the conditions of imperialism and post-colonialism, cultural prejudices, national imagination, "the cancel culture", revaluation of thecultural role of Ukraine). Cultural studies of these issues will strengthen the discussions around the issues of a better political order and theformation of post-colonial cultural policy in Ukraine.
Keywords: international cooperation in the field of culture; cultural diplomacy; cultural policy; Russian-Ukrainian war; post-colonialism; cultural identity